Consultancy skills in the light of emotional intelligence and communication skills of students specialised in human resources consultancy (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2020)
In our research we examined two groups of students specialised in human resources studying at University of Győr. We analysed the self-reflective communication developmental plans of 32 students (group 1) because we wanted to learn which communication needs they could identify and are ready to overcome. We also looked at the emotional intelligence of 44 students (group 2) drawing on Bar-On’s model which focuses on the harmony of intrapsychic and interpsychic skills. After comparing the two areas we could identify relations between the self- reflective description of communication and empathy, self-esteem, adaptability and handling stress and emotions. There are also links with age-related characteristics, and it points at the importance of learning through life experience while becoming an effective consultant.